Enhanced Visible-Light-Driven Photocatalytic Activity of ZnAl Layered Double Hydroxide by Incorporation of Co2+ - Deyang Li; Lihui Fan; Min Qi; Yanming Shen; Dongbin Liu; Shifeng Li (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
Co-doped ZnAl layered double hydroxides (LDH) were papered by coprecipitation. The prepared samples were characterized by multiple techniques including X-ray Diffraction (XRD), Brunauer−Emmett−Teller (BET) surface area, Scanning Electronic Microscopy (SEM), Transmission Electron Microscopy (TEM), X-ray Photoelectron Spectroscopy (XPS) and UV−Vis Diffuse-Reflectance Spectroscopy (UV−Vis DRS). The incorporation of Co2+ into the ZnAl LDH sheets as CrO6 octahedron forms a new energy level which contributes for the excitation of electrons under visible light. The doped Co2+ at a reasonable content also serves as photo-generated charges separator and improves the visible light photocatalytic activity of ZnAl LDH. A degradation mechanism based on the hydroxyl radical as the active species was proposed.